ANALISIS RESPONSIVENESS PELAYANAN KESEHATAN DI INSTALASI RAWAT INAP RUMAH SAKIT NASIONAL DIPONEGORO SEMARANG - Dian Febrina Hutauruk; Septo Pawelas Arso; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
One of the goals of health systems according to WHO is to increase the responsiveness of the health system, which responsiveness is fulfillment of non-medical aspects related to how people are treated and how the environmental conditions in which the person being treated. Low utilization rates of health care in inpatient, and based on a questionnaire completed by the patient hospitalized complaints were still found on some aspects responsiveness be the background for the assessment of the responsiveness of health care in Inpatient RSND. This study aimed to describe the eight domains of responsiveness as well as determine the level of responsiveness of health care in inpatient care unit RSND. This study design was a cross sectional study with a quantitative approach and supported by qualitative approach. The results of the research found Responsiveness level of health care in Inpatient RSND was 81.1%. Percentage value of responsiveness from the eight domains is greatest consecutive patient convenience of 99,4%, confidentiality 98.3%, 90% visited the conveniences, the choice of service provider 86.7%, 88.3% hospitality officer, patient involvement 88.3%, prompt to attention 83.3%, and the clarity of information 65%. The conclusion of this study is the responsiveness of health care in inpatient care RSND Installation is good, and has met the target set by the Ministry of Health. However, there are still some respondents who are less responsive because there are still health workers are less friendly, patient feels health information obtained is less clear than health workers, patients can not get access to health services (lab) easily, his old time use patients to get a visit from the doctor, the patient has not been able to choose their own health officers, and not the presence of reading materials in the treatment room.